Biofuntional nanoparticle formation and folate-targeted antitumor effect of heparin-retinoic acid conjugates - Oh, In-hyeok; Cho, Kwang Jae; Tran, Thanh Huyen; Huh, Kang Moo; Lee, Yong-kyu (Macromolecular research, 2012)
Heparin-retinoic acid (HR) and heparin-folic acid-retinoic acid (HFR) amphiphilic bioconjugates were synthesized for the development of an actively targeted drug delivery system for cancer therapy. The HR and HFR bioconjugates were synthesized by chemical conjugation via amide linkages of the carboxyl groups of heparin and the amine groups of aminated retinoic acid (RA) and aminated folic acid (FA). The chemical structures of HR and HFR were confirmed by proton nuclear magnetic resonance. The coupling ratio of RA to heparin could be modulated by varying the feed molar ratio of RA to heparin. In aqueous media, HR and HFR bioconjugates self-aggregated to form nanoparticles through the hydrophobic RA interactions. The size, critical aggregation concentrations, and morphologies of HR and HFR nanoparticles were evaluated using dynamic light scattering, fluorescence spectrophotometry, and scanning electron microscopy, respectively. The sizes of the HR and HFR nanoparticles ranged from 80 to 220 nm according to the coupling ratio of RA. In vitro experiments showed that the HFR nanoparticles selectively recognized a folate receptor-positive cancer cell line (KB cells) and displayed higher cytotoxicity compared to free RA and HR nanoparticles. This enhanced cytotoxicity was not observed in folate receptor-negative A549 cells. In a human tumor xenograft nude mouse model, HFR nanoparticles reduced the tumor volume compared to HR nanoparticles or free RA without any signs of toxicity. These results proved that HFR nanoparticles have great potential for cancer targeting and treatment.